Element dkt_cst for analysis of laminated anisotropic plates/Elementas dkt_cst sluoksniuotų anizotropinių plokštelių analizei - Michnevič, Edvard; Belevičius, Rimantas (Journal of Civil Engineering and Management, 2000)
The new finite element of multilayered built up with an arbitrary series of layers plate for plate bending problem is formulated on the ground of widely used, effective finite element Discrete Kirchhof Theory (DKT). The material of each layer is supposed to be different and orthotopic. Triangular element has 6 d.o.f.’s at each of 3 nodal points: 3 displacements and 2 rotations about co-ordinate axes. The 6th fictitious rotation about axis perpendicular to the element is also introduced due to numerical requirements. The element takes into account all the in-plane/out-of-plane effects except the shear. The element could find an application in the slab bending problems or in the plate, where the shear influence could be neglected, bending problems. The numerical examples are presented. Present solutions are compared with available analytical and numerical solutions. Article in Lithuanian. First Published Online: 26 Jul 2012